2013
DOI: 10.1185/03007995.2013.866545
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and tolerability of low-dose oral oxycodone/naloxone added to anticonvulsant therapy for noncancer neuropathic pain: an observational analysis

Abstract: c i a l D i s t r i b u t i o n U n a u t h o r i z e d u s e p r o h i b i t e d . A u t h o r i s e d u s e r s c a n d o w n l o a d , d i s p l a y , v i e w a n d p r i n t a s i n g l e c o p y f o r p e r s o n a l u s eCurrent Medical Research & Opinion Vol. 30, No. 4, 2014, 555-564 0300-7995 Article RT-0359. R1/866545 doi:10.1185/03007995.2013.866545 All rights reserved: reproduction in whole or part not permitted Results:Of 200 patients (mean age 65.9 years; 54% female) with NP included in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Two large‐scale observational studies included a total of 1,688 patients with neuropathic pain, receiving OXN PR at mean starting doses of 24.4 mg/day and 16 mg/day, respectively (concomitant gabapentin/pregabalin was permitted) . In these “real‐life” settings, OXN PR provided clinically relevant improvements in pain, functional impairment, and BFI scores compared with prior therapy, and was reported to be well tolerated . These findings are supported by a third large‐scale observational study of OXN PR (mean starting dose 15/7.5 mg/day; 19% received concomitant anticonvulsants) in 1,051 patients with constipation (37% had received prior opioid analgesia), of whom approximately 85% had chronic, moderate‐to‐severe neuropathic pain .…”
Section: Literature Searchmentioning
confidence: 74%
See 1 more Smart Citation
“…Two large‐scale observational studies included a total of 1,688 patients with neuropathic pain, receiving OXN PR at mean starting doses of 24.4 mg/day and 16 mg/day, respectively (concomitant gabapentin/pregabalin was permitted) . In these “real‐life” settings, OXN PR provided clinically relevant improvements in pain, functional impairment, and BFI scores compared with prior therapy, and was reported to be well tolerated . These findings are supported by a third large‐scale observational study of OXN PR (mean starting dose 15/7.5 mg/day; 19% received concomitant anticonvulsants) in 1,051 patients with constipation (37% had received prior opioid analgesia), of whom approximately 85% had chronic, moderate‐to‐severe neuropathic pain .…”
Section: Literature Searchmentioning
confidence: 74%
“…While several RCTs of OXN PR have included some patients with moderate‐to‐severe neuropathic pain, the effectiveness and tolerability of OXN PR in this setting was specifically investigated in 4 studies identified in our literature search (see Table ). Two large‐scale observational studies included a total of 1,688 patients with neuropathic pain, receiving OXN PR at mean starting doses of 24.4 mg/day and 16 mg/day, respectively (concomitant gabapentin/pregabalin was permitted) . In these “real‐life” settings, OXN PR provided clinically relevant improvements in pain, functional impairment, and BFI scores compared with prior therapy, and was reported to be well tolerated .…”
Section: Literature Searchmentioning
confidence: 99%
“…The observed improvement in QoL and patient’s satisfaction is in agreement with previous results, showing that attenuation of neuropathic pain after opioids improves mood and sleep. 48 , 49 …”
Section: Discussionmentioning
confidence: 99%
“…This result suggests development of a collateral circulation due to portal vein thrombosis, and naloxone directly reaching the central nervous system and evoking withdrawal symptoms. 89 Numerous other studies have demonstrated clinical effectiveness of OXN in patients with chronic nonmalignant pain, 67 , 68 , 79 , 80 , 83 , 84 , 90 95 cancer-related pain, 96 99 and postoperative pain. 100 , 101 …”
Section: Targeted Treatment Of Oibdmentioning
confidence: 99%